2018
DOI: 10.1016/j.jbankfin.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Oil volatility risk and expected stock returns

Abstract: After the …nancialization of commodity futures markets in 2004-05 oil volatility has become a strong predictor of returns and volatility of the overall stock market.Furthermore, stocks'exposure to oil volatility risk now drives the cross-section of expected returns. The di¤erence in average return between the quintile of stocks with low exposure and high exposure to oil volatility is signi…cant at 0.66% per month, and oil volatility risk carries a signi…cant risk premium of -0.60% per month. In the post…nancia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 75 publications
(46 reference statements)
3
34
0
Order By: Relevance
“…Authors employ asymmetric causality approach and find the short run causal relationship between oil price and price level. Christoffersen and Pan (2017) analyzes the oil price volatility risk and expected stock returns. They find oil price volatility risk carries a significant risk-premiums per month and also report that a rise in oil price ambiguity causes the performance of financial intermediaries.…”
Section: Literature Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Authors employ asymmetric causality approach and find the short run causal relationship between oil price and price level. Christoffersen and Pan (2017) analyzes the oil price volatility risk and expected stock returns. They find oil price volatility risk carries a significant risk-premiums per month and also report that a rise in oil price ambiguity causes the performance of financial intermediaries.…”
Section: Literature Analysismentioning
confidence: 99%
“…The average OVX price appears to be 37.59 indicates that investors' overreaction to crude oil price uncertainty was on the higher side. The average change of OVX and returns appears to be positive signifies overburden on the hedge fund, and a higher premium for the put USO-ETF options (e.g., Christoffersen & Pan, 2017). WTI crude oil price on an average calculated 81.39 with negative average returns.…”
Section: Quantile Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of the literature examined the relationship between oil price and equity markets [9,[20][21][22][40][41][42]. Mensi et al [43] studied the volatility transmission between the Standard and Poor's 500 Index (S&P 500) and the commodity markets.…”
Section: Equity and Commodities Markets And Oilmentioning
confidence: 99%
“…Mensi et al [43] continued to verify the interdependence between oil prices and major stock indices such as S&P 500 and Dow Jones Industrial Average (DJIA). Other studies also identified the return spillover from S&P 500 to WTI [42,44]. Moreover, Zhou et al [45] evaluated the co-movement between the volatility of the equity market proxied by S&P 500 and the oil market proxied by USO from 2007 to 2016.…”
Section: Equity and Commodities Markets And Oilmentioning
confidence: 99%